THE CENTRAL CHARACTER’S SOCIAL BACKGROUND AND ITS RELATION TO DOMESTIC CONFLICT IN KEVIN KWAN’S RICH PEOPLE PROBLEM - Aristi, Sri Nida; Ratih P, Shita Dewi; Widisanti, Ni Made (Journal Albion : Journal of English Literature, Language, and Culture, 2023)
The thesis entitled "The Central Character’s Social Background and Its Relation to Domestic Conflict in Kevin Kwan’s Rich People Problem " is the main topic of this research. The novel itself was published in 2017. The method used in this research is descriptive analysis method by analyzing and describing the central character’s social background and how it is related to the cause of domestic conflicts through the use of intrinsic and extrinsic elements. The results showed that a person's social background affects their life and character which gave rise to domestic conflict, meaning that domestic conflicts can be caused by different social backgrounds even though they come from the same family lineage.  In this particular case, the domestic conflict that occurred because of such condition, was in the form of a fight over the family's main inheritance, namely Tyersall Park.Keywords: social background, central characters, habitus, wealth background